The Effects of Internal Marketing on Customer Satisfaction in Chinese Restaurant Industry A Case Study of Haidilao Hot Pot Restaurant - Lu, Qing (2013)
In service industry, many enterprises believe that external marketing is the most effective way to attract customers. However, they ignore that employees are the service providers whose attitudes and behaviors largely determine customers’ perception towards this corporation. Therefore, enterprises, especially in restaurant industry must implement a good internal marketing since it can motivate employees to create greater additional value for customers thus leading to high customer satisfaction. This thesis focuses on the case study of a famous Chinese hot pot restaurant named Haidilao. This study emphasizes the importance of internal marketing in restaurant industry as well as the effect of employee satisfaction on customer satisfaction. Restaurant enterprises must understand and fulfill frontline employees’ needs, particularly spiritual needs, thus gaining high employee satisfaction and loyalty. Well-treated employees can help corporations to enhance additional service value, emotional value and brand value, ultimately leading to high customer satisfaction. The purpose of this thesis is to increase the awareness of the importance of internal marketing and to gain a clear idea of how restaurant enterprises use internal marketing to motivate employees and how satisfied employees help improve customer satisfaction.